Improved longitudinal analysis of single lane concrete box-girder bridge decks for IRC loading - Thampi, Ambili; Menon, Devdas (Journal of Structural Engineering, 2024)
In the prevailing design practice, for the longitudinal analysis of the box-girder, the box-girder is commonly modelled as a beam and simple beam analysis (SBA) is used for determining the longitudinal forces. These calculated longitudinal forces are then enhanced by about 10 percent to account for the effects of distortion, warping and shear lag. In the present study, a number of simply supported box-girder bridges have been analyzed by both SBA and three-dimensional finite element analysis (3DFEA) for different parameters (span of the bridge L, spacing between webs b, height of the web d, location of load expressed in terms of x/b, and the ratio of web-to-fl ange thickness tw/tf). It is seen that all these parameters affect the “correction factors” to be applied to the results of SBA. This paper presents a comprehensive set of “correction factors” to the design forces obtained by SBA for various classes of IRC loading. Also, the existing practice of design is reviewed and improvements suggested for rational and economical design.